A New Hope: A Hermaphroditic Nematode Enables Analysis of a Recent Whole Genome Duplication Event. (3rd December 2022) - Wighard, Sara S; Athanasouli, Marina; Witte, Hanh; Rödelsperger, Christian; Sommer, Ralf J
Abstract: Whole genome duplication (WGD) is often considered a major driver of evolution that leads to phenotypic novelties. However, the importance of WGD for evolution is still controversial because most documented WGD events occurred anciently and few experimental systems amenable to genetic analysis are available. Here, we report a recent WGD event in the hermaphroditic nematode Allodiplogaster sudhausi and present a comparison with a gonochoristic (male/female) sister species that did not undergo WGD. Self-fertilizing reproduction of A. sudhausi makes it amenable to functional analysis and an ideal system to study WGD events. We document WGD in A. sudhausi through karyotype analysis and whole genome sequencing, the latter of which allowed us to 1) identify functional bias in retention of protein domains and metabolic pathways, 2) show most duplicate genes are under evolutionary constraint, 3) show a link between sequence and expression divergence, and 4) characterize differentially expressed duplicates. We additionally show WGD is associated with increased body size and an abundance of repeat elements (36% of the genome), including a recent expansion of the DNA-hAT/Ac transposon family. Finally, we demonstrate the use of CRISPR/Cas9 to generate mutant knockouts, whereby two WGD-derived duplicate genes display functional redundancy in that they both need to be knocked out to generate a phenotype. Together, we present a novel experimental system that is convenient for examining and characterizing WGD-derived genes both computationally and functionally.